Effect Of Orius insidiosus (Hemiptera: Anthocoridae) And Spinosad (Conserve®) On Western Flower Thrips, Frankliniella occidentalis (Thysanoptera: Thripidae), Populations In Transvaal Daisy Flowers - Motolai, Gergely; Cloyd, Raymond A.; Herrick, Nathan J. (My University, 2018)
Western flower thrips (WFT), Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is a major insect pest of greenhouse-grown horticultural crops. Greenhouse producers typically apply insecticides to suppress WFT populations. However, continual reliance on insecticides can lead to the development of resistant in WFT populations. The insidious flower bug, Orius insidiosus (Say) (Hemiptera: Anthocoridae), is a commercially available predatory bug of WFT that offers an alternative to using insecticides for WFT suppression. Therefore, we investigated the efficacy of one or two O. insidiosus adults compared to spray applications of the standard insecticide, spinosad (Conserve®) in suppressing WFT adult populations in transvaal daisy (Gerbera jamesonii), cut-flowers under greenhouse conditions. Percent adult WFT mortality was significantly lower when one or two O. insidiosus adults were released into the flowers (mean range: 32 to 34%; n=747), compared to the untreated and water control (8 to 9%; n=431). The highest percent mortality of WFT adults was associated with the spinosad (Conserve®) treatment (100%; n= 203).
Keywords: Fall 2018